Renal system modeling for nuclear medicine studies - Zhang, Lei (2008)
Dynamic renal scintigraphy is a useful tool in nuclear medicine to evaluate the function of kidneys for diagnostic and prognostic purposes. Renal scintigraphic images provide information on the radioisotope distribution in kidney. By placing the regions of interest (ROIs) on the scintigraphic images, the renal time-activity curves (TACs) can be obtained. Further quantitative analysis of these renal TACs can derive physiological parameters to help physicians in diagnosing renal diseases. In this thesis, models for kidney are developed to analyze the TACs.